Lateral Habenula Beyond Avoidance: Roles in Stress, Memory, and Decision-Making With Implications for Psychiatric Disorders - Baker, Phillip M.; Mathis, Victor; Lecourtier, Lucas; Simmons, Sarah C.; Nugent, Fereshteh S.; Hill, Sierra; Mizumori, Sheri J. Y. (Frontiers in Systems Neuroscience, 2022)
In this Perspective review, we highlight some of the less explored aspects of lateral habenula (LHb) function in contextual memory, sleep, and behavioral flexibility. We provide evidence that LHb is well-situated to integrate different internal state and multimodal sensory information from memory-, stress-, motivational-, and reward-related circuits essential for both survival and decision making. We further discuss the impact of early life stress (ELS) on LHb function as an example of stress-induced hyperactivity and dysregulation of neuromodulatory systems within the LHb that promote anhedonia and motivational deficits following ELS. We acknowledge that recent technological advancements in manipulation and recording of neural circuits in simplified and well-controlled behavioral paradigms have been invaluable in our understanding of the critical role of LHb in motivation and emotional regulation as well as the involvement of LHb dysfunction in stress-induced psychopathology. However, we also argue that the use of ethologically-relevant behaviors with consideration of complex aspects of decision-making is warranted for future studies of LHb contributions in a wide range of psychiatric illnesses. We conclude this Perspective with some of the outstanding issues for the field to consider where a multi-systems approach is needed to investigate the complex nature of LHb circuity interactions with environmental stimuli that predisposes psychiatric disorders.